2019
DOI: 10.1016/j.redox.2019.101231
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-glutamylcysteine synthetase and tryparedoxin 1 exert high control on the antioxidant system in Trypanosoma cruzi contributing to drug resistance and infectivity

Abstract: Trypanothione (T(SH) 2 ) is the main antioxidant metabolite for peroxide reduction in Trypanosoma cruzi ; therefore, its metabolism has attracted attention for therapeutic intervention against Chagas disease. To validate drug targets within the T(SH) 2 metabolism, the strategies and methods of Metabolic Control Analysis and kinetic modeling of the metabolic pathway were used here, to identify the steps that mainly control the pathway fluxes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
(129 reference statements)
2
22
0
Order By: Relevance
“…After 13 days of interaction, almost all the cells have been infected. From these results, we concluded that the fraction of infected cells after 18 h of the initial cell-parasite interaction can be used as an estimate for the parasite invasion efficiency, in agreement with former results 12,[18][19][20] .…”
Section: Resultssupporting
confidence: 90%
“…After 13 days of interaction, almost all the cells have been infected. From these results, we concluded that the fraction of infected cells after 18 h of the initial cell-parasite interaction can be used as an estimate for the parasite invasion efficiency, in agreement with former results 12,[18][19][20] .…”
Section: Resultssupporting
confidence: 90%
“…Finally, GBD had an IC 50 = 66 ± 12 μM. For comparison, under similar exposure protocols, the IC 50 for benznidazole was 12 ± 2 μM [ 35 ] whereas for NFX the value was 3 ± 0.6 μM (Aketzalli Silva Carmona & Emma Saavedra, unpublished results). In addition, the compounds were evaluated on human foreskin fibroblasts (HFF1) to measure cytotoxicity; the effects on these cells are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the established relationship between melarsoprol and trypanothione, the specific mode of melarsoprol cell killing remains unknown (24). Because the biosynthetic and redox utilization pathways contain enzymes unique to Trypanosomatids, they have been broadly explored as drug targets against American trypanosomes and Leishmania species (15,(28)(29)(30)(31)(32).…”
Section: Traditional Methods Of Overexpression Library Formation By Cmentioning
confidence: 99%
“…6). The essential gene encoding gglutamylcysteine synthetase (GSH1, Tb927.10.12370)(41), which is the rate-limiting step of trypanothione biosynthesis(28,32,33,42), was 191-fold overrepresented in melarsoprol survivors(TABLE 2). Overexpression of GSH1 in T. brucei and other Trypanosomatids increases the concentration of intracellular trypanothione and has been shown to promote melarsoprol resistance under laboratory conditions(33).…”
mentioning
confidence: 99%